2021
DOI: 10.3390/ijerph182010986
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Dietary Fat with Polyunsaturated Fatty Acids Attenuates the Lipopolysaccharide-Induced Hepatic Inflammation in Sprague-Dawley Rats Fed a High-Fat Diet

Abstract: In this study, we investigated whether the partial replacement of dietary fat with polyunsaturated fatty acids (PUFAs) ameliorated the lipopolysaccharide (LPS)-induced hepatic inflammation in rats fed a high-fat diet. Male Sprague-Dawley rats were divided into three groups and provided each of the following diets: (1) high-fat diet (HFD), (2) HFD with perilla oil (PO), and (3) HFD with corn oil (CO). After 12 weeks of dietary intervention, the rats were intraperitoneally injected with LPS (5 mg/kg) from Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 88 publications
(110 reference statements)
3
19
0
Order By: Relevance
“…These results may imply that a lower ratio of n -6/ n -3 PUFAs inhibits hepatic TG accumulation and inflammation; therefore, we postulate that PO may mitigate hepatic function abnormalities in LPS-injected ob/ob mice. These results were observed in other mouse LPS models in our previous study [ 33 , 34 , 38 ]. To study how pathological remodeling affects liver tissue function, aspartate aminotransferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) levels were measured.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results may imply that a lower ratio of n -6/ n -3 PUFAs inhibits hepatic TG accumulation and inflammation; therefore, we postulate that PO may mitigate hepatic function abnormalities in LPS-injected ob/ob mice. These results were observed in other mouse LPS models in our previous study [ 33 , 34 , 38 ]. To study how pathological remodeling affects liver tissue function, aspartate aminotransferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) levels were measured.…”
Section: Resultssupporting
confidence: 89%
“…Other pathological stimuli for atherosclerosis may include hypertension, chronic kidney disease, aging, hyperglycemia, and inflammatory responses. Previously, we reported that the LPS injection induced hyperlipidemia accompanied by increased TG, TC, HDL-C, and non-HDL-C levels and CVD expectancy in experimental rodents [ 33 , 38 ]. The administration of LPS can lead to rapid and transitory increases in pro-inflammatory cytokines such as TNF-α and IL-6 in mammals [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid composition of the experimental diets was determined by methyl esterification of boron trifluoride (BF 3 )-methanol [ 48 ]. Briefly, 0.1 g of sample was placed in a test tube, followed by the addition of 0.5 mL of heptadecanoic acid (C17:0; 1 mg/mL hexane).…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were extracted from the liver using the method of Bligh and Dyer [ 54 ] with slight modifications [ 48 ]. Briefly, 0.1 g of tissue was added to a chloroform/methanol (1:2, v / v ) solution and centrifuged at 1800× g for 5 min to obtain the lower lipid layer containing TG and TC for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation